1987
DOI: 10.1007/bf00713378
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical study of epidermal Langerhans cells and dermal dendritic cells in benign and malignant skin lesions characterized by a dermal lymphoid infiltrate consisting either of B-cells or T-cells

Abstract: Skin biopsies from 43 patients with a rather dense dermal lymphoid infiltrate of either inflammatory or neoplastic nature have been investigated. We studied the number, distribution and immunophenotype of epidermal Langerhans cells and dermal dendritic cells. As previously reported, differences in epidermal Langerhans cell and dermal dendritic cell numbers between skin biopsies with a B-cell infiltrate and skin biopsies with a T-cell infiltrate were found, dendritic cells being more numerous in the latter. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1988
1988
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Others suggested that the abundance of CD1a + cells might be useful in the differentiation between CTCL and pseudo-CTCL [9]. Drijkoningen et al [3] quantified DC (LC and DDC) and their distributions in benign and malignant cutaneous lymphoproliferations. They found that DC were more numerous in T-cell infiltrates than B-cell infiltrates.…”
Section: Discussionmentioning
confidence: 98%
“…Others suggested that the abundance of CD1a + cells might be useful in the differentiation between CTCL and pseudo-CTCL [9]. Drijkoningen et al [3] quantified DC (LC and DDC) and their distributions in benign and malignant cutaneous lymphoproliferations. They found that DC were more numerous in T-cell infiltrates than B-cell infiltrates.…”
Section: Discussionmentioning
confidence: 98%
“…Drijkonigen et al (17) analyzed their own results and data from the literature and found that inflammatory infiltrates consisting of dendritic cells and T cells in the skin and around the small vessels are similar to the secondary T nodules of the paracortex of the reactive lymph nodes. The latter can be correlated with the dendritic cel!-T cell clusters of the primary immune response observed in vitro (17). This delayed type of T cell immune response can be induced by a number of chemical and physical effects or pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…77 The papillary dermis features an intense lymphocytic perivascular infiltrate consisting of T cells and dendritic cells, as is seen in many inflammatory dermatoses. 78 Most of the lymphocytes are CD4 1 and CD8 1 T cells; cytotoxic T cells seem to be a special feature of EBVinduced GCS. 42 In the nonvesicular form, the epidermis may have modest acanthosis and focal parakeratosis and spongiosis.…”
Section: Histologymentioning
confidence: 99%